Cerebrospinal Pharmacokinetic Analysis and Pharmacodynamic Evaluation of Ceftriaxone in Pediatric Patients with Bacterial Meningitis - Onita, Tetsushu; Ikawa, Kazuro; Ishihara, Noriyuki; Tamaki, Hiroki; Yano, Takahisa; Morikawa, Norifumi; Naora, Kohji (Journal of clinical pharmacy and therapeutics, 2024)
What Is Known? and Objective. Ceftriaxone has been widely used to treat bacterial meningitis in pediatric patients. Ceftriaxone dosing regimens of 80–120 mg/kg/day have been recommended for bacterial meningitis in pediatric patients, and the usual duration of therapy is 7–14 days. Although the target site for meningitis is cerebrospinal fluid (CSF), a CSF pharmacokinetic (PK) model in pediatric patients has not been reported. We aimed to develop a CSF PK model of ceftriaxone, using not only serum but also CSF concentration data, and to evaluate the appropriateness of dosing regimens for pediatric patients with bacterial meningitis. Methods. The population PK model was developed by simultaneously fitting serum and CSF data from pediatric patients described in nine published articles. Probabilities of attaining a pharmacodynamic target (100% T > MIC, 100% of time that drug concentrations above the minimum inhibitory concentration) in CSF were estimated for some dosing regimens. Results and Discussion. Twenty-four pediatric patients with meningitis were the subjects for PK modeling (0.52–13 years old, and 3.5–50 kg of body weight). Sixty-eight serum concentrations and 98 CSF samples were used to develop the CSF PK model. The CSF/serum concentration ratio at the same sampling time was 0.0628 ± 0.0689. Age was not a statistically significant covariate in the PK parameter. In the CSF PK model, 40–60 mg/kg q12 h achieved a target attainment probability >90% against causative bacteria for bacterial meningitis. However, 4-h infusion (rather than 0.5-h infusion) dosing regimens were required for efficacy against antimicrobial-resistant bacteria with high MICs. What Is New? and Conclusion. Ceftriaxone-dosing regimens with prolonged infusion times might be reasonably effective for treating antimicrobial-resistant pathogens in empiric therapy.